2018
DOI: 10.1021/acs.molpharmaceut.8b00454
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated Accumulation of Novel Fluorine (19F)-Labeled Bile Acid Analogues in Gallbladders of Fibroblast Growth Factor-15 (FGF15)-Deficient Mice

Abstract: Our work has focused on defining the utility of fluorine (19F)-labeled bile acid analogues and magnetic resonance imaging (MRI) to identify altered bile acid transport in vivo. In the current study, we explored the ability of this approach to differentiate fibroblast growth factor-15 (FGF15)- deficient from wild-type (WT) mice, a potential diagnostic test for bile acid diarrhea, a commonly misdiagnosed disorder. FGF15 is the murine homologue of human FGF19, an intestinal hormone whose deficiency is an underapp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…These methods are likely insufficient to study dynamic, posttranslational changes in ASBT activity, necessitating the development of real-time methods. Several recent approaches have been developed to quantify the aspects of bile acid physiology in -real time (76,115,263,311,389,392,(397)(398)(399). Additionally, a recent bioluminescence-based approach relying on a CA-luciferin-conjugated probe has shown promising results for measuring real-time ASBT activity in vitro and in isolated intestinal epithelial cells (377).…”
Section: Posttranscriptional Regulation Of Asbtmentioning
confidence: 99%
“…These methods are likely insufficient to study dynamic, posttranslational changes in ASBT activity, necessitating the development of real-time methods. Several recent approaches have been developed to quantify the aspects of bile acid physiology in -real time (76,115,263,311,389,392,(397)(398)(399). Additionally, a recent bioluminescence-based approach relying on a CA-luciferin-conjugated probe has shown promising results for measuring real-time ASBT activity in vitro and in isolated intestinal epithelial cells (377).…”
Section: Posttranscriptional Regulation Of Asbtmentioning
confidence: 99%
“…One study reported on the utility of fluorine (19F)-labeled bile acid analogs and magnetic resonance imaging (MRI) in identifying altered bile acid transport in mice. 10 Two groups of mice were compared: wild-type and FGF15-deficient mice (FGF15 is a murine homolog of human FGF-19). After dosing the animals orally, the researchers quantified 19F-labeled bile acid analog levels in the gallbladder, liver, intestine, and plasma using liquid chromatography.…”
Section: Streszczeniementioning
confidence: 99%
“…Additionally, the structural properties of CA-sar-TFMA and CA-lys-TFA permit their transport within the enterohepatic circulation since they are substrates for both ileal ASBT and the hepatic Na+/taurocholate co-transporting polypeptide (NTCP). Despite their different structures, these bile acid analogues performed alike, sufficiently to assess impaired bile acid transport within the enterohepatic circulation [ 25 ]. In our studies, incubation of CA-sar-TFMA and CA-lys-TFA with stool and gallbladder homogenates for up to 24 h revealed no significant degradation in either 19 F-bile acid analogue [ 25 ].…”
Section: Development Of 19 F-labeled Bile Acid Anamentioning
confidence: 99%
“…Despite their different structures, these bile acid analogues performed alike, sufficiently to assess impaired bile acid transport within the enterohepatic circulation [ 25 ]. In our studies, incubation of CA-sar-TFMA and CA-lys-TFA with stool and gallbladder homogenates for up to 24 h revealed no significant degradation in either 19 F-bile acid analogue [ 25 ].…”
Section: Development Of 19 F-labeled Bile Acid Anamentioning
confidence: 99%
See 1 more Smart Citation